(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This article aims to examine Umar Chapra’s thoughts on Islamic macroeconomics and their relevance in achieving inclusive and sustainable economic growth. This research uses a qualitative approach with a desk study to analyze Chapra’s key works and related literature on Islamic macroeconomics. The results show that Chapra based his economics on the principles of tawhid, khilafah, and justice, which are then translated into the goal of maqāṣid al-sharī‘ah, namely the achievement of falah (true welfare). He proposed the use of instruments such as zakat, waqf, and the profit-loss sharing (PLS) system to create a more equitable redistribution of wealth and reduce social inequality. Chapra also criticized the interest system (riba) that concentrates wealth and risk in certain groups. The implication of these findings is that Islamic economics, particularly as developed by Chapra, provides a framework for more inclusive and sustainable fiscal and monetary policies. However, challenges such as the transparency of zakat governance and the quality of Islamic banking need to be addressed. Further research examining the empirical impact of applying Chapra’s principles to economic policy in Muslim countries could strengthen the application of this concept in practice.